Semi‐refined carrageenan film incorporated with α-tocopherol: Application in food model - Khadijah Husna, Abd Hamid; Wan Amnin, Wan Yahaya; Nur 'Alia Zaini, Mohd Saupy; María Pilar, Almajano; Nurul Aini, Mohd Azman (Blackwell Publishing Ltd., 2019)
Semi‐refined carrageenan (SRC) film plasticized with glycerol and incorporated with α‐tocopherol was prepared for food packaging application. Functional characterization, thermal stability, and microstructure of SRC‐based films were analyzed. The effects of antioxidant α‐tocopherol from SRC‐based film were studied based on thiobarbituric acid‐reactive substance assay, metmyoglobin assay, and pH value in food model (meat patties) for 12 days of storage. The development of lipid oxidation was delayed in the meat patties wrapped with antioxidant films during the storage with the final value of 0.68–0.37 mg malondialdehyde/kg sample. A less than 50% brown color development (metmyoglobin) of the meat patties wrapped with antioxidant film was observed in the first nine days of storage. Hence, the incorporation of α‐tocopherol into the SRC‐based film could be an alternative way to prolong the shelf life of food product, reducing the use of synthetic preservative directly into food product.